HISTORICAL-ECONOMIC KNOWLEDGE AS THE BASIS OF THE THEORETICAL LEVEL OF ECONOMIC THINKING - Tufetulov, Aidar M.; Hadiullina, Gulnara N.; Shakirov, Rival R.; Zayats, Andrey S. (Gênero & Direito, 2019)
Economic theory as an independent science arose in the period of the formation of modern market relations. The economic thought history as a separate branch in the system of economic sciences took shape in the first half of the XIX century. The tradition of Russian economic thought at all stages of its development was attention to historical trends and factors of socio-economic development. The reason for this is in the specifics of Russia's socioeconomic and spiritual development. ХIХ century is characterized by the struggle of old and new trends in the economic system of Russia. In these conditions, representatives of various branches of economic thought appealed to the historical experience of the country and humanity in order to prove the truth of their position. The paper presents an analysis the historical process of emergence, development, struggle, and the changing of economic ideas. The main attention is paid to the analysis of the main directions of modern economic theory underlying the decision-making at macro and microeconomic levels. The content of the historical and economic knowledge functions: worldview, practical, axiological, factual and methodological, is defined. The necessity of studying the provisions of alternative economic schools is substantiated, what is considered as a prerequisite for the formation of general cultural and professional competencies of specialists in the field of economics